Semantic dogmatics in outline: Cornelius Ernst's 'meaning of meaning' as Michael Polanyi's absent doctrine of God - Keenan, O (2018)
Cornelius Ernst’s doctrine of God as the meaning of meaning corresponds to the implicit theological ontology around which Michael Polanyi’s fiduciary epistemology coheres. Conversely, Polanyi’s account of cognitive dynamics supplements Ernst’s metaphysics of meaning with a concrete account of the involvement of the embodied subject. Both Polanyi and Ernst seek to re-orientate their respective disciplines of theological and natural science within an intrinisicist perspective of meaning. Ernst’s theological ontology secures a thematic metaphysics in which the unity of the semantic cosmos is located in the divine triunity of Meaning. This is achieved by a doctrine of creation, in which the world is always already charged by God’s self-communication (corresponding to Polanyi’s efforts to generate a biosemiotic ontology). Within this proposed ontology of meaning, the unicity of theological knowledge is safeguarded by an account of the incarnation as an ‘ontological metaphor’, which is non-identically repeated in the act of faith. As an ontological metaphor, faith has a vocative character, addressing God in an act of worship that is simultaneously doxological and doxastic. This is framed by the action of the Holy Spirit, mediated by the Church: doctrinal frameworks are semantic tools that are indwelt in worship in such a way that theological knowledge becomes connatural. The result is a ‘semantic dogmatics in outline’ which emphasises the pedagogical role of theology, balancing the necessary integrity of dogmatics with its proper eschatological provisionality.